Is medial soft tissue laxity more important than lateral laxity after total knee arthroplasty? - Mizu-uchi, Hideki; Ishibashi, Shojiro; Kawahara, Shinya; Yara, Takuro; Nakashima, Yasuharu; D’Lima, Darryl D. (The knee, 2025)
The optimal range of soft tissue balance that consistently leads to better patient outcomes has yet to be identified in total knee arthroplasty. This study aimed to analyze the effect of soft tissue tightness on Knee Society Score by grouping patients by extent of medial or lateral laxity and mediolateral balance. Varus and valgus laxity were measured using stress radiographs for 95 varus-deformed osteoarthritis knees (82 patients). The joint line angle and the joint gap were calculated using digital measurement software and computer-aided design models of the implants. We divided patients based on medial and lateral joint gaps into three groups: tight (<3 mm), intermediate (3–6 mm), and loose (>6 mm). Postoperative joint line angles averaged 5.1 (1.8)° for varus stress and −4.6 (2.1)° for valgus stress. Medial joint gaps under valgus stress were 3.5 (1.6) mm and lateral joint gaps under varus stress were 3.9 (1.4) mm. The intermediate medial laxity group had the highest knee scores, and satisfaction scores in particular were significantly better than the two other groups. Patients with intermediate lateral laxity achieved significantly greater postoperative flexion compared with that in the two other groups. There were no significant differences in Knee Society Scores or range of motion among the patients grouped by mediolateral balance. Achieving intermediate medial laxity is more impactful than equal mediolateral balance for better postoperative outcome. Clinically undetectable medial tightness may be more common without an accurate ligament balancer during the surgery.